2017
DOI: 10.17116/otorino201782571-76
|View full text |Cite
|
Sign up to set email alerts
|

The genetic aspects of occupational hearing impairment

Abstract: This article was designed to be the overview of the current literature publications concerning the identification of the genetic markers of susceptibility to the noise-induced loss of hearing. The analysis of these data has demonstrated that the major gene polymorphisms associated with the development of this pathological condition are localized in the genes encoding for the antioxidant systems, potassium homeostasis, and adhesion molecules as well as in the genes involved in intercellular coupling, the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Carlsson et al analyzed genetic polymorphism in the 10% most susceptible and 10% most resistant extremes of 1200 Swedish noise-exposed workers to investigate whether genetic variation is associated with susceptibility to NIHL. In their study no significant differences were found between 103 noise-susceptible and 114 noise-resistant Swedish workers from the point of view of GSTM1 and GSTT1 polymorphism [6]. Palodetto et al showed that polymorphism in GSTM1 and GSTT1 have no influence on ototoxicity of aminoglycosides, which seem to involve similar oxidative stress mechanis like NIHL [14].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Carlsson et al analyzed genetic polymorphism in the 10% most susceptible and 10% most resistant extremes of 1200 Swedish noise-exposed workers to investigate whether genetic variation is associated with susceptibility to NIHL. In their study no significant differences were found between 103 noise-susceptible and 114 noise-resistant Swedish workers from the point of view of GSTM1 and GSTT1 polymorphism [6]. Palodetto et al showed that polymorphism in GSTM1 and GSTT1 have no influence on ototoxicity of aminoglycosides, which seem to involve similar oxidative stress mechanis like NIHL [14].…”
Section: Discussionmentioning
confidence: 81%
“…So, it is possible in studies that did not find association of GST gene and NIHL, like our study, the noise exposure levels to which the majority of study workers have been exposed over the years did not reach the critical level needed to activate the antioxidant system, and therefore differences in their antioxidant systems are unlikely to show up in their findings. However, it is possible that difference exists when subgroups (noise exposure levels, noise exposure times) be evaluated separately [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation